2018
DOI: 10.1155/2018/9362041
|View full text |Cite
|
Sign up to set email alerts
|

The Use of SPEI and TVDI to Assess Temporal-Spatial Variations in Drought Conditions in the Middle and Lower Reaches of the Yangtze River Basin, China

Abstract: Droughts represent the most complex and damaging type of natural disaster, and they have taken place with increased frequency in China in recent years. Values of the standardized precipitation evapotranspiration index (SPEI) calculated using station-based meteorological data collected from 1961 to 2013 in the middle and lower reaches of the Yangtze River Basin (MLRYRB) are used to monitor droughts. In addition, the SPEI is determined for different timescales (1, 3, 6, and 12 months) to characterize dry or wet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Ideally, future research would evaluate morphological traits (such as leaf area, plant height, and specific stem [root] length), photosynthesis and respiration rates, physiological processes (non-structural carbohydrates and other C-N metabolic indicators) as well as reproductive characteristics (seed mass and seed number), to construct the trait correlation network at the whole-plant level to illustrate comprehensively the adaptation of plants to various environmental factors. Our 26 sampled lakes are located in the middle and lower reaches of Yangtze floodplain, where the average annual temperature and precipitation is 14-18 • C and 1,000-1,400 mm, respectively (Chen et al, 2018). Small thermal and moisture gradients in this region limit the exploration of latitudinal patterns of nutrient allocation strategies among organs on a large spatial scale.…”
Section: Further Studies Of Nutrient Partitioning Among Organsmentioning
confidence: 99%
“…Ideally, future research would evaluate morphological traits (such as leaf area, plant height, and specific stem [root] length), photosynthesis and respiration rates, physiological processes (non-structural carbohydrates and other C-N metabolic indicators) as well as reproductive characteristics (seed mass and seed number), to construct the trait correlation network at the whole-plant level to illustrate comprehensively the adaptation of plants to various environmental factors. Our 26 sampled lakes are located in the middle and lower reaches of Yangtze floodplain, where the average annual temperature and precipitation is 14-18 • C and 1,000-1,400 mm, respectively (Chen et al, 2018). Small thermal and moisture gradients in this region limit the exploration of latitudinal patterns of nutrient allocation strategies among organs on a large spatial scale.…”
Section: Further Studies Of Nutrient Partitioning Among Organsmentioning
confidence: 99%
“…The Yangtze River Basin is the third-largest river basin in the world, with a total drainage area of approximately 1.8 million km 2 , accounting for 18.8% of China's land area [32]. The annual precipitation in the MLRYRB, which was chosen as the study area (as shown in Figure 1), is 1000-1400 mm, and the distribution of precipitation decreases from southeast to northwest.…”
Section: Study Areamentioning
confidence: 99%
“…Among them, the most commonly used drought indices were the Standardized Precipitation Index (SPI) [8] and the Palmer Drought Severity Index (PDSI) [9]. SPI is based on the cumulative probability of precipitation at different time scales and was developed to reflect the impact of changes in water resources on groundwater and agriculture during the study period, thereby revealing the degree of drought in the study area [10], which is often used to capture the drought situation at multiple scales [11]. PDSI is a comprehensive index that uses precipitation and air temperature data to evaluate drought status, and is widely employed to study agricultural drought [12].…”
Section: Introductionmentioning
confidence: 99%